A Study on the Cardiac Manifestations and Their Short-Term Outcome in Patients with Kawasaki Disease in an Indian Population - Gopalan Nair Rajesh; S Prasanth; Haridasan Vellani; Jomy Vadasseril Jose (Journal of the Indian Academy of Echocardiography & Cardiovascular Imaging, 2022)
Objectives: This study aimed to assess the prevalence of cardiac manifestations and their short-term outcome in patients with Kawasaki disease (KD) in an Indian population. Methods: This single-center prospective study enrolled a total of 56 consecutive patients with classic and incomplete KD. Six months and 1-year clinical outcomes were analyzed. Results: Fifty-six consecutive patients were enrolled in the study and followed up for 1 year. About 87% completed 6 months follow-up. A diagnosis of complete KD was made in 41 (73%) patients and incomplete KD in 15 (27%). Cardiac manifestations were present in 25% of patients with KD. Coronary involvement was observed in 11 (20%) patients by either Japanese Ministry of Health Criteria or a z score of ≥2.5. Nonpurulent conjunctivitis was significantly higher among children with cardiac involvement (79% vs. 43% P = 0.04). The mean value of erythrocyte sedimentation rate (ESR) was significantly higher among patients with cardiac involvement (101.92 ± 22 vs. 74.26 ± 28.6; P = 0.002). An ESR value of >100 mm/hr was predictive of cardiac involvement (P = 0.03). The mean serum glutamic-pyruvic transaminase value was higher among those with cardiac involvement (P = 0.008). Coronary dilatation got resolved in 3 months in 73% of patients. Valvular regurgitations, aortic root involvement, and depressed left ventricular myocardial function were not observed in the population studied. Conclusions: Cardiac manifestations were present in 25% of patients with KD, 20% of children had coronary involvement in the form of an aneurysm, or ectasia. About 73% of patients with coronary dilatation got resolved in 3 months. Significant valvular heart diseases, aortic root involvement, and myocardial contractile dysfunction were not seen in the studied population with KD.